ANALISIS SOSIOLOGIS KEHIDUPAN BIDUANITA DI BANDAR LAMPUNG - Syaputra, Rio Tri; Damayantie, Anita (SOCIOLOGIE, 2013)
Prostitution as a social problem while the views of causality and its origin can not be known with certainty, but until now a lot of prostitution mation encountered in everyday life, therefore, the public in general that would condemn the practice of prostitution should do measures to stop or at least be able to know and inform the public impact will arise from the songstress with a negative outlook in the society due to action of the ladies on stage and the clothes she wears often bring sensation for the audience who saw it. Bandar Lampung city is the provincial capital of Lampung Lampung Province where perkonomian centered in the city of Bandar Lampung, in the city where many entertainment events serving the ladies who presented entertainment held in the community. Formulation of the problem in this research is the reason for women to be ladies and decisions impact the lives of the ladies in their daily lives. This type of research used in this study is qualitative in-depth interviews. Based on the results of research and discussion by the author it could be concluded that, the reason why they became a hobby and the songstress is due to economic factors.Keywords: Songstress